The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/ma10111231
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization-Induced Surface Cracks of Carbon Ions Irradiated 6H-SiC after Annealing

Abstract: Single crystal 6H-SiC wafers with 4° off-axis [0001] orientation were irradiated with carbon ions and then annealed at 900 °C for different time periods. The microstructure and surface morphology of these samples were investigated by grazing incidence X-ray diffraction (GIXRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Ion irradiation induced SiC amorphization, but the surface was smooth and did not have special structures. During the annealing process, the amorphous SiC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In experimental research of recent years, Jones [82,83] uncovered an interstitial type dislocation called end-of-range (EOR) damage through TEM micrographs, just below the crystalline / amorphous interface by Ge + -implanted silicon. Ye et al [84] illustrated recrystallization process of carbon irradiated 6H-SiC, and found the volume shrinkage and the anisotropy of the new born crystal during annealing process generated internal stress, which not only produced a large number of dislocation walls but also caused the initiation and propagation of cracks. Hence, the crack propagation or glide of pre-existing basal-plane dislocations can be suppressed by improving the temperature gradient inside the annealing furnace in actual processing [85].…”
Section: Structural Evolution During Annealing Recrystallizationmentioning
confidence: 99%
“…In experimental research of recent years, Jones [82,83] uncovered an interstitial type dislocation called end-of-range (EOR) damage through TEM micrographs, just below the crystalline / amorphous interface by Ge + -implanted silicon. Ye et al [84] illustrated recrystallization process of carbon irradiated 6H-SiC, and found the volume shrinkage and the anisotropy of the new born crystal during annealing process generated internal stress, which not only produced a large number of dislocation walls but also caused the initiation and propagation of cracks. Hence, the crack propagation or glide of pre-existing basal-plane dislocations can be suppressed by improving the temperature gradient inside the annealing furnace in actual processing [85].…”
Section: Structural Evolution During Annealing Recrystallizationmentioning
confidence: 99%
“…Owing to the advanced physical and chemical stability properties, silicon carbide (SiC) and SiC‐fiber‐reinforced SiC matrix composites, have been regarded as a promising material for advanced nuclear energy application . It has been extensively investigated irradiation effects in the high purity SiC and composite, including neutron, ion, and electron irradiation . In addition, the corrosion resistance of the SiC materials has been investigated in the high‐pressure and high‐temperature water and molten salt …”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of mold flux isothermal crystallization involving nucleation and growth are analyzed through the Johnson–Mehl–Avrami (JMA) model [27,28,29,30]. According to the JMA model, the volume fraction of crystals X ( t ) is given by:Xfalse(tfalse)=1expfalse(ktnfalse) where X ( t ) is the relative degree of crystallinity at a given time t , including the incubation time, n is the Avrami exponent, which is associated with the nucleation and growth mechanism, and k is the effective crystallization rate constant, which is dependent on the temperature and the rate of nucleation and crystal growth.…”
Section: Resultsmentioning
confidence: 99%